AN ANALYSIS OF INFLUENCES THAT ATTRACT YOUNG CONSUMERS IN THE NETHERLANDS’ INTEREST ON BUYING REFURBISHED ELECTRONIC DEVICES - Adiningtyas, Susanti Kisworowati; Tesselhof, Kees (Diponegoro Journal of Accounting, 2024)
Refurbished electronic devices are a relatively new and emerging topic in the IT world. Its newness causes people, young consumers included, to not know and be aware of it. Which means that the young consumers in the Netherlands do not always have interest in buying refurbished electronic devices (REDs). This is an issue for companies whose business revolves around REDs. This research paper aims to analyse the influences that can attract young consumers’ interest in buying REDs. The analysis of this study was conducted using both literature and interviews. The finding discusses the young consumers’ level of knowledge and awareness of this topic. Furthermore, there is also discussion of the solution that can help the company attract young consumers’ interest in buying REDs.